PENGGUNAAN MEDIA PEMBELAJARAN CERITA PERANG OBOR 3D DALAM MASALAH KETERAMPILAN MENULIS PADA KELAS V SD 2 KARANGGONDANG - Rahayu, Sepvi; Fajrie, Nur; Kironoratri, Lintang (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
This research aims to determine the effect of students' writing skills with learning media story war 3D torch in class V SD N 2 Karanggondang 3 D media is realized with pop up book media. Data collection techniques use technique interviews, observations, tests, and documentation. Analysis of the data used covers qualitative data analysis with subject 21 students . Enhancement results Study influenced by management learning and activities student Based on study above the media is solution for overcome skills write paragraphs, research and analysis to Indonesian language learning skills write, can withdrawn conclusion that results Study about material influence change environment physique to mainland experience improvement, It is seen in condition beginning student error write student decrease. Besides from class average gain, increase results you can learn too seen from percentage achievement KKM value obtained students, achieve 100% KKM completion